PERAN STUKTUR PENGENDALIAN INTERNAL TERHADAP PROSEDUR PEMBERIAN KREDIT UNTUK MENCEGAH TERJADINYA KREDIT BERMASALAH: (Studi Empiris Pada Bank BTPN Cabang Bangkalan) - M. Lukman Assidiki (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2017)
This research aims to know what is the role of internal controlling structure towards credit funding procedures to prevent problematic credit. Method used in this research is qualitative descriptive. Bank BTPN Bangkalan branch has high Non Performing Loan value or problematic credit which is above Bank Indonesia's standards. This research is did by direct field observing, interviewing credit department's employees and directors, and documents like financial statement accountability to obtain the credit data. Triangulation of data is used to make conclusion.The result of this research is the Bangkalan bank has implemented good credit funding and internal controlling , however, there is an insufficient monitoring did by the bank towards debitor's business condition after credit is funded resulting in that company is not able to pay the credits (Non Performing Loan) that had been dealt beforehand, and that there is a duty and positional capture by the loan officer that handles credit analysis and debitor's guaranteed transactions.